Study on the gut microbiota, HPA, and cytokine levels in infantile spasms - You, Jiajia; Liu, Li; Pan, Xiongfeng; Wu, Liwen; Tan, Lihong; Zhou, Changci; Fang, Siwei; Xiao, Zhenghui; Qiu, Jun (Frontiers in Immunology, 2024)
The mechanisms driving infantile spasms progression are not well understood, we aim to investigate the changes and correlations in the gut microbiota, hypothalamus-pituitary-adrenal axis hormones, and inflammatory cytokines in children with infantile spasms before and after treatment to offer a reference for future pathogenesis research.Children with infantile spasms admitted to our hospital were recruited into the case group. The case group was divided into pre-treatment group (Group A, n=14), 2 weeks after treatment group (Group B), and 1 month after treatment group (Group C). Whereas healthy children with the same sex ratio as the case group were recruited into the control group (Group D, n=14). Three stool samples and blood samples were collected before treatment, 2 weeks after treatment and 1 month after treatment. The serum samples were analyzed by cytometric bead array (CBA), enzyme-linked immunosorbent assay (ELISA), and chemiluminescent immunoassay (CLIA) to measure the levels of hypothalamus- pituitary-adrenal axis hormones and cytokines. The collected stool samples were sequenced by 16S rDNA.Results: Pre-treatment group demonstrated elevated corticotropin-releasing hormone (CRH), IL2, IL4, IL6, IL17α，and these decrease with treatment. Level of CRH was lower in effective group than that in the ineffective group. Sutterellaceae in the pre-treatment group was lower than that in the control group. Lachnospiracea_incertae_sedis was positively associated CRH concentration (P ＜ 0.05). Sutterellaceae after treatment was negatively associated with IL-2 and TNF-α(P＜0.05).Our study found that imbalance of the gut microbiota may be involved in the pathogenesis of infantile spasms and is related to response to adrenocorticotropic hormone (ACTH). Lachnospiraceae and Lachnospiracea_incertae_sedis might get involved in the disease onset. Sutterellaceae might be linked to children's improved health.